(untitled) (Conferencea, 2023)
This scientific article investigates the language-pragmatic features inherent in the translation of Uzbek anecdotes into English. Anecdotes, as a form of oral literature, carry cultural nuances and linguistic peculiarities that pose unique challenges for translators. This study aims to shed light on the pragmatic aspects of this translation process, examining how cultural context, humor, and linguistic elements are navigated to ensure effective communication in the target language.